1988
DOI: 10.1088/0022-3727/21/6/025
|View full text |Cite
|
Sign up to set email alerts
|

New evidence against the presence of peak IV in the TL and PTTL glow curves of heavily annealed TLD-100

Abstract: Presents some additional evidence against the recent identification of peak IV in the TL and PTTL glow curves of heavily annealed TLD-100. Deconvolution analysis of the glow curves, produced by annealing for progressively increasing durations at 150 degrees C, permits the identification of a new and relatively broad peak, centered at 162 degrees C. This should not be confused with peak IV (182 degrees C), despite their relative proximity in temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

1988
1988
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
0
6
1
Order By: Relevance
“…performed emission spectra measurements 011 the TL from LiF:Mg, Ti. The dominant emission appeared to be related t o Ti, as is generally asserted [5], but there was clear evidence of perturbation of this emission by the Mgrelated defects. These observations received support from McKeever [C;] who examined the spectra of X-ray-induced luminescence and concluded that the aggregation state of the Mg was affecting the luminescence emission.…”
Section: Townsend Et Al [4]mentioning
confidence: 51%
See 1 more Smart Citation
“…performed emission spectra measurements 011 the TL from LiF:Mg, Ti. The dominant emission appeared to be related t o Ti, as is generally asserted [5], but there was clear evidence of perturbation of this emission by the Mgrelated defects. These observations received support from McKeever [C;] who examined the spectra of X-ray-induced luminescence and concluded that the aggregation state of the Mg was affecting the luminescence emission.…”
Section: Townsend Et Al [4]mentioning
confidence: 51%
“…The spectra have been obtained by illuminating the sample with 200 nm light. This is believed t o correspond to absorption from T i complexes [ 5 ] , absorption from which is evident before irradiation (see curve 2 in Fig. 1 b).…”
Section: Resultsmentioning
confidence: 85%
“…There are other dramatic dissimilarities between peaks 4 and 5 . For example, phototransfer processes do not fill peak 4 traps, so that this peak is not observed in the TLD-100 PITL glow curve [12]. McKeever [25], on the basis of x-ray-induced luminescence and TL spectral emission studies has suggested that the major defect responsible for TL peak 5 is a Mg trimer/Ti complex.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, even the width and shape of glow peak 5 has been shown to be batch dependent, leading to significant differences in the deduced values of the activation energy, E , and the 'attempt to escape' frequency, s, of peak5 (111. Of course, different thermal treatments are also known to induce very different glow curve shapes [12], apparently due to the possibility of various clustering reactions between Mg*+-vacancy dipoles.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Delgado et al [33] expressed some doubts about the correct identification of peak 4. These doubts were based on the relatively important difference in temperature between the peak produced by the heavy annealing and peak 4 in unannealed LiF:Mg, Ti.…”
Section: Introductionmentioning
confidence: 99%